Long term outcome of Wilms’ tumor in tertiary care hospital - T., Jeevarathi; Vadivelu, Gomathi (International Surgery Journal, 2020)
Background: Nephroblastoma, or Wilms’ tumor, is an embryonal tumor that develops from remnants of the immature kidney. It is the most common renal tumor of childhood. The aim is to analyze the long term outcome in Wilms’ tumor in perplex situations as double moiety and to correlate with multiple organ defects. Methods: It is a combined perspective and retrospective study that pediatric urology outpatient department (OPD) at the Institute of Child Health and Hospital for Children, Madras Medical College, Chennai. The study included patients with Wilms, who attended the pediatric surgery during the ten years, from March 2008 to February 2011. The patients were subjected to detailed clinical examination and relevant investigations were performed. Results: Among patients with stage I–II fumarate hydratase (FH) tumors, the relative risk (RR) of relapse and death were increased for loss of heterozygosity (LOH) 1p only (RR=2.2 for relapse; RR=4.0 for death), for LOH 16q only (RR=1.9 and RR=1.4), and LOH for both regions (RR=2.9 and RR=4.3) in comparison with patients lacking LOH at either locus. Conclusions: Stage I and II have a good prognosis. Stage III and IV need close surveillance since they have a high rate of recurrence. Stage V has a bad prognosis. Stage IV Wilms need lung irradiation. Neoadjuvant chemotherapy reduces tumor spillage in stage III and IV.